PENDAMPINGAN IDENTIFIKASI DAN INVENTARISASI OBJEK PEMAJUAN KEBUDAYAAN DAN CAGAR BUDAYA KABUPATEN ASMAT - Abdi K, Simon; Marlina Flassy,; Usman Idris,; Enrico Y. Kondologit, (JURNAL PENGABDIAN MANDIRI, 2024)
This community service article is an activity that aims to identify and inventory Objects of Cultural Advancement and Cultural Heritage found in Asmat Regency. In the implementation of this activity in collaboration with the local government of Asmat Regency. The method of implementing the activity consists of stages, namely preparation, data collection and dissemination of results. The results of the identification and inventory show that there is a need to increase or increase the number of cultural actors for the preservation of Cultural Advancement Objects. Cultural institutions must be formed that will focus on working in advancing culture. Then the Government really needs to provide infrastructure for the development, preservation and utilisation of Cultural Advancement Objects and Cultural Heritage.